2021
DOI: 10.3389/fvets.2020.617259
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Gut Microbiota and Its Correlation With Short Chain Fatty Acids and Bioamine in Piglets at the Early Growth Stage

Abstract: The change characteristics of intestinal microbial succession and the correlation with the production of two important types of bacterial metabolites (short chain fatty acids and bioamine) in piglets during the early stage were fully explored in this study. Six piglets from different litters with the same birth time were selected, weighted and euthanized at 1, 7, 14, 21, 28, 35, and 42 days of age. During this stage, the piglets grew quickly with gradual increases in blood levels of growth hormone and insulin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 39 publications
4
23
2
Order By: Relevance
“…Franklin et al showed that pig intestinal SCFA concentrations and microbial populations are influenced by weaning age ( Franklin et al, 2002 ). Recently, Qi et al also found that total SCFA concentration was increased as pigs aged (from lactation and early nursery; Qi et al, 2020 ). Hence, we speculated that the influence of age on SCFAs may be related to it.…”
Section: Discussionmentioning
confidence: 98%
“…Franklin et al showed that pig intestinal SCFA concentrations and microbial populations are influenced by weaning age ( Franklin et al, 2002 ). Recently, Qi et al also found that total SCFA concentration was increased as pigs aged (from lactation and early nursery; Qi et al, 2020 ). Hence, we speculated that the influence of age on SCFAs may be related to it.…”
Section: Discussionmentioning
confidence: 98%
“…It has been demonstrated that the intestinal flora is involved in the development of UC and affects its severity. In particular, intestinal flora dysbiosis promotes intestinal inflammation and an immune response (49), which may be key for the induction of IBD (50). When UC occurs, the intestinal flora becomes disordered, the abundance of harmful bacteria increases, and the number of beneficial bacteria decreases (51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbial structure of individual digestive chambers cannot be fully revealed by fecal samples alone. Qi et al ( 2021 ) reported that the alpha-diversity of ileal microbiota was lower compared with that of the colon in pigs, and different dominant genera were identified in colonic and ileal microbial communities. However, severe discomfort and suffering to the animals are unavoidable when invasive approaches are employed to collect these samples.…”
Section: Discussionmentioning
confidence: 99%